PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SEBLAK JOMBANG MELALUI STRATEGI KEPEMIMPINAN - Anis Nur Azizah; Moh. Syamsul Falah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The most important factor in developing policies and even tactics to solve challenging problems is leadership. Islamic boarding school institutions need a caregiver who has the spirit of a leader. The success of Islamic boarding schools cannot be separated from the leadership of caregivers who continue to carry out various strategies that are considered effective and efficient in achieving the goals of the institution they lead and produce students as human resources with character. The Indonesian nation has entered the industrial era 4.0 which will have an impact on the existence of Islamic boarding schools as Islamic educational institutions. Islamic boarding schools have a big role in helping to educate the nation's children by providing quality education. This research aims to examine in more depth how Islamic boarding school leadership strategies are in forming the character of their students at the Salafiyah Syafi'iyah Islamic Boarding School Seblak Jombang. This research tries to analyze three things, namely: 1) What is the Islamic boarding school leadership strategy at the Salafiyah Syafi'iyah Islamic Boarding School Seblak Jombang? 2) How is the character of students formed at the Seblak Jombang Salafiyah Syafi'iyah Islamic Boarding School? 3) What is the Islamic boarding school leadership strategy in forming the character of students at the Salafiyah Syafi'iyah Islamic Boarding School Seblak Jombang? This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The data analysis technique uses three stages, namely data reduction, data presentation and verification. From the research results, it is known that the Islamic boarding school leadership strategy at the Salafiyah Syafi'iyah Islamic Boarding School in Seblak Jombang, Islamic boarding school caregivers implement 5 strategies, namely: exemplary strategy, strategy for enforcing rules, strategy for implementing the yellow book recitation curriculum, strategy for getting used to religious services and strategy for organizing additional extras. Then the character formation of students at the Salafiyah Syafi'iyah Seblak Jombang Islamic Boarding School is carried out using several methods, namely the method of applying example, the habituation method, the method of advice and punishment, and the training method. The type used by caregivers while leading is the democratic type and the average student at the Salafiyah Syafi'iyah Islamic Boarding School Seblak Jombang has a character that is religious, disciplined, responsible, brave, independent, creative, devout and of course has good morals. The conclusion drawn is that Islamic boarding school leaders here have 5 strategies and these strategies have a big influence on the formation of the students' character.